The Relationship Between Health Service Quality And General Poly Patient Satisfaction At Uptd Tipar Health Center In Sukabumi City - Ida, Ida (Journal of Midwifery and Nursing, 2025)
Health is a basic need for everyone, a person certainly needs good health in his life to be able to carry out his daily activities without problems. Factors that affect patient satisfaction are the Tipar Health Center in Sukabumi City's patient satisfaction rate and the quality of its medical services. Service quality Is the standard of quality required to satisfy client requests. Patient satisfaction is the level of feeling a patient feels arising from the effectiveness of medical care received following comparing with what he expected. This type of research is collerational research. The population is General Poly patients who visit the Tipar Health Center in Sukabumi City with a sample of 340 people. Sampling using axial sampling. The results of the validity and reliability test of the Service Quality variable which has 25 question items and Patient Satisfaction which has 25 questions are declared valid and reliable. Hypothesis analysis using somers'd test. The results show that the quality of health services is generally good and patients are satisfied. The p value obtained in the Somers'd test is 0.001, which means that H0 is rejected that there is a relationship between the quality of health services and patient satisfaction. The study determined a relationship between the quality of health services and patient satisfaction at the UPTD Tipar Community Health Center, Sukabumi City. It is hoped that the Puskesmas will be a strategy to improve the quality of health services and will be a review resource for the satisfaction of the patient in receiving health services